2021
DOI: 10.48550/arxiv.2110.07628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leaky exciton condensates in transition metal dichalcogenide moiré bilayers

Benjamin Remez,
Nigel R. Cooper

Abstract: We show that the "dark condensates" that arise when excitons form a Bose-Einstein condensate in a material with an indirect bandgap are not completely dark to optical emission. Rather, such states are "leaky condensates" in which optical emission is facilitated by many-body interactions. We analyze the properties of these leaky condensates in the context of twisted bilayers of transition metal dichalcogenides, which host strongly interacting excitons and an indirect bandgap. We show that, even though excitonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…The moiré periodicity and the Coulomb repulsion can lead to the localization of an exciton in each moiré unit cell. Such an effect on the exciton condensate can be described by the moiré Bose-Hubbard (BH) Hamiltonian [54,55],…”
Section: (B)) ε Ementioning
confidence: 99%
“…The moiré periodicity and the Coulomb repulsion can lead to the localization of an exciton in each moiré unit cell. Such an effect on the exciton condensate can be described by the moiré Bose-Hubbard (BH) Hamiltonian [54,55],…”
Section: (B)) ε Ementioning
confidence: 99%
“…Now the exciton condensation is still a hot topic, and various varieties, including pure optically active excitons, Moiré exciton, and trion-polaritons, have been investigated. [142][143][144] Additionally, the condensation of excitons into an electronhole liquid (EHL) has also been extensively investigated. [145] At low densities, excitons are noninteracting and behave like an ideal gas, which are hence referred to as "free excitons."…”
Section: Exciton Phase Transitionmentioning
confidence: 99%
“…It is demonstrated that the MPDs lead to non-uniform dielectric properties in moiré superlattices, such as interlayer charge transfer, polarizability, and the evolution of the local band gap due to an applied field. Although the concept of a local band gap is in general ill-defined, it has been used to estimate the potential landscape for interlayer moiré excitons [17][18][19][20][21][22], giving rise to novel exciton dynamical, optical and many-body phenomena [23]. While the theory of lattice relaxation and its influence on structural properties of moiré superlattices is well-known [24,25], the practical details required to perform efficient calculations are typically omitted.…”
Section: Introductionmentioning
confidence: 99%